La biodiversité : un besoin de clarification - Lecointre, Guillaume (Comptes Rendus Biologies)
Ever since the term “biodiversity” was first defined, it has been used in a mixed way, referring on the one hand to the characterisation of living organisms (which is the domain of systematics), and on the other hand to their functional interactions (which are the domain of ecology). This ambiguity has led to the terms biodiversity and ecosystem being used almost synonymously, a mistake that is both epistemologically and politically damaging. To clear up this confusion, the term biodiversity should be reserved for what we observe when we characterise or discover “what there is” (a task for systematics) at the three infra-specific, specific and supra-specific levels, and the term ecosystem should be reserved for what we observe when we are interested in the functional interactions (“what it does”, a task for ecology) between living organisms, and between the latter and the abiotic environment.